A Level‐of‐Service Concept for Planning Future Water Supply Projects under Probabilistic Demand and Supply Framework1. (10th June 2015) - Asefa, Tirusew; Adams, Alison; Wanakule, Nisai
Abstract One of the most challenging tasks of water supply utilities is planning the timing and quantity of new water supply sources as demand for water consumption grows. Many water supply utilities target on meeting 100% of their customers' needs based on scenario‐based deterministic demand projections numbers even though there are uncertainties in both supply and demand values. This may result in under or overly conservative approach in assessing future needs. In this article, a level‐of‐service concept is introduced to capture a utility's willingness to accept a given level of risk, plan for it, and invoke a management strategy during extreme events than build a facility to accommodate those in planning for new water supply sources. Accounting for uncertainties in both supply and demand help quantify reliability by achieving a prescribed level of service. The major benefit of such an approach for planning future water supply is that it allows policy makers to evaluate the use of adaptive water management strategies and develop supply in an incremental fashion as demand warrants it. For example, if a given level of service cannot be reliably met with the existing system at a future time t, an incremental water supply project would come online to bring the required reliability level up but no more.